2006
DOI: 10.1136/oem.2005.025916
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for work related asthma in young adults

Abstract: The prevalence of work related asthma was high (4.2%), and was associated with low schooling, probably because of low socioeconomic level. The disease may therefore be a consequence of poverty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 46 publications
1
44
1
1
Order By: Relevance
“…Lower level of education (1-8 years of schooling) with an OR of 7.1 was reported to be associated with occupational asthma in the Brazilian study (19) and illiteracy (OR=2.1) in the Pakistani study.10 In the present study even though low level of education emerged significant in the bivariate analysis, it did not remain same when adjusted for confounding factors.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Lower level of education (1-8 years of schooling) with an OR of 7.1 was reported to be associated with occupational asthma in the Brazilian study (19) and illiteracy (OR=2.1) in the Pakistani study.10 In the present study even though low level of education emerged significant in the bivariate analysis, it did not remain same when adjusted for confounding factors.…”
Section: Discussioncontrasting
confidence: 48%
“…Atopy was reported to be significantly associated with occupational asthma in the British Columbian study (11), the Brazilian study (19) and the studies on animal shelter workers (20) and dental health care workers.17 In the British Columbian study family history was observed to be a risk factor for BA both before and after employment in the current industry (11). However, according to Ameille et al (9) role of genetics lacks consistency in being reported as a significant factor.…”
Section: Discussionmentioning
confidence: 86%
“…The levels of allergen in these workplaces were not associated with primary outcomes: sensitization, symptoms, asthma, or BHR. Asthma, defined by symptoms and a positive bronchial challenge test, showed no increased prevalence as compared with other prevalence studies in this country and region 20) . The lack of association between exposure and asthma may be consequence of the healthy worker effect, as discussed below.…”
Section: Discussionmentioning
confidence: 71%
“…Some of these analyses have already been published. [7][8][9][10] The tests and measurements were carried out in a healthcare setting with easy access to medical facilities. The examinations were performed at the university hospital in the city of Ribeirão Preto, in the northwestern region of the state of São Paulo, Brazil.…”
Section: Samplementioning
confidence: 99%
“…8 The ECRHS questionnaire was developed for use among young adults aged 20 to 44 years, to explore asthma symptoms in young adults. We used questions of the ECRHS questionnaire to explore asthma symptoms.…”
Section: Respiratory and Occupational Questionnairesmentioning
confidence: 99%